2008
DOI: 10.1196/annals.1425.003
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Health and Lives of People Living in Slums

Abstract: Urban poverty, ill health, and living in slums are intrinsically interwoven. Poverty is multidimensional and there is no agreement on a universal definition. UN-HABITAT has introduced an operational definition of slums that is restricted to legal aspects and excludes the more difficult social dimensions. The World Health Organization definition is more comprehensive and uses a health and social determinants approach that is strongly based on the social conditions in which people live and work. Health and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Based on this review, we found 182 possible evaluations but narrowed them down to thirty-two by selecting those that had at least one additional published report on the project. We also narrowed our search by focusing upon “integrated” or multi-sectoral interventions, which aimed to address physical, social and urban governance concerns in informal settlements [26,27]. We focused our search on multi-sectoral interventions because we hypothesized that these might offer reviews and/or evaluations of several environmental and social impacts.…”
Section: Methods: Review Of Urban Slum Upgrading Projectsmentioning
confidence: 99%
“…Based on this review, we found 182 possible evaluations but narrowed them down to thirty-two by selecting those that had at least one additional published report on the project. We also narrowed our search by focusing upon “integrated” or multi-sectoral interventions, which aimed to address physical, social and urban governance concerns in informal settlements [26,27]. We focused our search on multi-sectoral interventions because we hypothesized that these might offer reviews and/or evaluations of several environmental and social impacts.…”
Section: Methods: Review Of Urban Slum Upgrading Projectsmentioning
confidence: 99%
“…While this typology helps us to understand the morphology of informal settlements in the city, it also reinforces that informal settlements and slums emerge and flourish in locations that are at higher risk to climate change and environmental hazards, such as land slips, steep slopes, flood-prone areas and poor drainage [40][41][42] (see Figure 2). In developing countries, it is estimated four out of every ten non-permanent houses are located in areas subject to landslides, flooding and other natural disasters [43], with informal settlements in such areas with non-compliant technical codes and construction increasingly vulnerable to extreme natural events [44]. reinforces that informal settlements and slums emerge and flourish in locations that are at higher risk to climate change and environmental hazards, such as land slips, steep slopes, flood-prone areas and poor drainage [40][41][42] (see Figure 2).…”
Section: The Diverse Challenges Of Informal Settlements and Slumsmentioning
confidence: 99%
“…reinforces that informal settlements and slums emerge and flourish in locations that are at higher risk to climate change and environmental hazards, such as land slips, steep slopes, flood-prone areas and poor drainage [40][41][42] (see Figure 2). In developing countries, it is estimated four out of every ten non-permanent houses are located in areas subject to landslides, flooding and other natural disasters [43], with informal settlements in such areas with non-compliant technical codes and construction increasingly vulnerable to extreme natural events [44]. Demand for affordable housing and proximity to jobs in inner city locations exerts pressure on existing landowners, settlers and their housing stock, and as such intensification of informal settlements and the emergence of slums are inevitable.…”
Section: The Diverse Challenges Of Informal Settlements and Slumsmentioning
confidence: 99%
“…These include poor outcomes for maternal health, higher rates of teenage pregnancy [3] and financial barriers to child health care in Nairobi [4]; high rates of respiratory conditions in children under the age of five years due to poor environmental conditions in Karachi slums [5]; and lower body mass index amongst the poorest child slum dwellers in Dhaka [6]. Studies and reviews highlight the multi dimensional nature of poverty and ill health in urban slums including the diversity and heterogeneity of social structure and health access [7], and recommend a range of responses ranging from targeted medical interventions, to capacity building and skills transfer, to infrastructure development and improved networking of NGOs, municipal governments and private practitioners [8]. …”
Section: Introductionmentioning
confidence: 99%